Pay to Play: Looking Beyond Direct Compensation and Towards Paying College Athletes for Themselves - Luke Tepen (Washington University Journal of Law & Policy, 2021)
The NCAA prohibits its athletes from profiting from their athleticism while playing in the league. As public support for this policy dwindles, the NCAA must respond. This Note analyzes the policy’s history and the potential constitutional challenge the NCAA could bring against the California law. Tepen urges the NCAA to act swiftly before it is constrained by each state’s own patch-work regulatory framework. By adopting California’s Fair Pay to Play Act, the NCAA can gain control before the government forces its hand. Tepen argues this proposal will best serve the interests of athletes, the NCAA, and fans alike.
Keywords: compensation; athlete; athletes; athletics; college; college athletics; college sports; sport; sports; NCAA; National Collegiate Athletic Association; pay to play; California; California Fair Pay to Play Act